PROBLEMATIKA PEMBELAJARAN TEMATIK INTEGRATIF DI MADRASAH IBTIDAIYAH IKHLAASUL ‘AMAL SEBAWI - Hesti Hesti; Aslan Aslan; Rona Rona (ADIBA : JOURNAL OF EDUCATION, 2022)
The curriculum as the wheel of education from year to year experiences challenges following technological developments, so that these challenges make teachers experience problems, both in delivering subjects to students and adjusting to curriculum desires, such as changing KTSP to K13. The study of this research is the field, where the research findings are; first, the problem of learning tools prepared by the teacher until its implementation and second, the problem of teacher assessment of students, although the three aspects assessed are cognitive, affective, and psychomotor, but the assessment tool has changed in terms of valuable input and description in assessing.